Evaluación del sistema de gestión de la producción en la UEB Villamar de la Empresa Pesquera Industrial de Caibarién (EPICAI) - Díaz Ferrer, Dayami (Universidad Central "Marta Abreu" de Las Villas, 2007)
The present investigation was made in the UEB Villamar of the Industrial Fishing Company of Caibarién, this company every year contributes with its activity, to the entrance from currencies to the country through the originating product export of the processing of marine species. The present investigation has, as main target, the implementation of a procedure for the evaluation of the Production Management System in the UEB Villamar that allows to determine the level of performance of this System, to make the critical analysis of the results and to develop directed plans of improvement towards the profit of competitive advantages. The evaluation of the Production Management System through indicators that measure their performance, constitutes the main result obtained in the accomplishment of the investigation, together with the proposal of plans of improvements for those aspects in which deficiencies were detected. Finally the feasibility of application of this procedure in companies pertaining to the manufacturing sector manages to verify itself since this Unit constitutes a representative sample of it.

La presente investigación se realizó en la UEB Villamar de la Empresa Pesquera Industrial de Caibarién, esta empresa cada año contribuye con su actividad, a la entrada de divisas al país a través de la exportación de productos provenientes del procesamiento de especies marinas. La presente investigación tiene como objetivo fundamental la implementación de un procedimiento para la evaluación del Sistema de Gestión de la Producción en la UEB Villamar, que permita determinar su nivel de desempeño, realizar el análisis crítico de los resultados y desarrollar planes de mejora encaminados hacia el logro de ventajas competitivas. La evaluación del Sistema de Gestión de la Producción a través de indicadores que miden su desempeño constituye el principal resultado obtenido en la realización de la investigación, unido a la propuesta de planes de mejoras para aquellos aspectos en los que se detectaron deficiencias. Por último logra comprobarse la factibilidad de aplicación de este procedimiento en empresas pertenecientes al sector manufacturero, ya que esta Unidad constituye una muestra representativa del mismo.
Keywords: Gestión; Sector Manufacturero; Especies Marinas; Producción; Caibarién; Empresa Pesquera Industrial